2019
DOI: 10.3390/ani9040158
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Vagina–Cervix Length Measurement in Evaluation of Future Reproductive Performance of Sows: A Preliminary Study under Commercial Conditions

Abstract: The length of the distal part of the internal reproductive tract seems to be related to the length and capacity of uterine horns, which is the most important anatomical property influencing litter size in sows. The aim of this study was to evaluate variation in vagina–cervix length (VCL) in gilts and differences in reproductive performance of sows according to VCL. The study was performed in a commercial farm using 221 gilts introduced into the breeding herd. Females were divided into three groups: (S) short (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although choline is known for its health benefits in adults, fetal development and other aspects of fertility [29], its specific role in the female reproductive tract and ovarian development has not yet been explored. Our findings demonstrate that choline increases reproductive tract development, which could increase future litter size, the number of live fetuses and the lifetime piglet production of female pigs [25,30]. In humans, the cervical length is inversely proportional to the risk of spontaneous preterm births in which those with the shortest cervical length have the highest risk of prematurity [31].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Although choline is known for its health benefits in adults, fetal development and other aspects of fertility [29], its specific role in the female reproductive tract and ovarian development has not yet been explored. Our findings demonstrate that choline increases reproductive tract development, which could increase future litter size, the number of live fetuses and the lifetime piglet production of female pigs [25,30]. In humans, the cervical length is inversely proportional to the risk of spontaneous preterm births in which those with the shortest cervical length have the highest risk of prematurity [31].…”
Section: Discussionmentioning
confidence: 69%
“…Oviduct length and ovary weight had no significant differences among treatment groups (Table 4, Ref. [25]). Overall backfat gain was lowest in the control group, with the Omega-3 group having significantly higher backfat gain compared to the control group (p < 0.05, Table 4), while the other groups had intermediate backfat gain.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The cervix of the first parity size is small [38], and whilst birthweight is often reduced also [39], foetal pelvic disproportion is the likely explanation for birth trauma in piglets born to sows of this youngest age. Even within parity, cervical size appears to be important [40]. In old sows however, birth trauma is due to reduced oxytocin levels and myometrial tone as discussed with reference to stillbirths in earlier paragraphs.…”
Section: Risk Factors For Birth Traumamentioning
confidence: 99%
“…The study of the reproductive tract of the gilt from birth to puberty showed important changes in the weight and length of the oviducts and the uterus when puberty was reached [20]. Recently, the length of vagina-cervix has been related to length and capacity of uterine horns [21,22]. A certain level of body condition would be needed for puberty onset in gilts [23]; also, fat mass was associated with puberty in female mammals [24].…”
mentioning
confidence: 99%